DECISION ANALYSIS NUMBER 3096 K / PID.SUS / 2018 OF CRIMINAL ACTION OF FRAUD AND FIRST TRAVEL MONEY WASHING - Permadi, Adhani Azhar (NOVUM : JURNAL HUKUM)
Cassation Decision Number 3096 K / Pid.Sus / 2018 regarding Fraud and Money Laundering Crime Cases committed by First Travel caused losses to First Travel pilgrims who had deposited money to First Travel either through agents or to First Travel directly. So that First Travel pilgrims who were victims of fraud and money laundering committed by First Travel did not get their money back. The purpose of this study was to determine the suitability of the principles of justice and the usefulness of the decision related to the First Travel Fraud and Money Laundering criminal cases. as well as to find out the legal remedies that First Travel pilgrims can take in order to recover compensation for the payment of Umrah fees that have been paid to First Travel. This research is a normative juridical legal research using a case, statutory and conceptual approach. The legal materials for this research consist of primary and secondary legal materials. The results showed that based on the principle of fairness and the benefit of the case cannot be justified. Because based on the theory of restorative justice, every consequence of a criminal act must prioritize the interests of the victim due to the crime. Judges in deciding cases in efforts of restorative justice may pay attention to Article 98 of the Criminal Procedure Code. Where the article regulates the mechanism for combining compensation with the prosecution of a criminal act so that the victim does not need to file a different lawsuit, and undergo a separate trial to obtain compensation. Legal remedies that can be taken by Jamaah First Travel are in the path of litigation, which is applying for PKPU and bankruptcy to First Travel.